Apoptosis in normal and osteoarthritic human articular cartilage - Heraud, F (2000)
OBJECTIVES—To investigate whether apoptosis occurs in osteoarthritis (OA), and if this phenomenon is modulated by human recombinant interleukin 1β (hrIL1β). METHODS—Human articular cartilage samples were obtained at the time of hip arthroplasty because of femoral neck fracture (normal cartilage) (n=4) or advanced coxarthrosis (OA cartilage) (n=14). Apoptotic chondrocytes, isolated by collagenase digestion and cultivated for 24 hours, or present in situ in frozen cartilage sections, were quantified by fluorescent microscopy using two apoptosis markers: the TUNEL reaction, which detects nuclear DNA fragmentation, and Annexin-V-fluos, which labels at the membrane level the externalisation of phosphatidylserine. RESULTS—In OA cartilage 18-21% of chondrocytes showed apoptotic features, compared with 2-5% in normal cartilage. The results were similar for the two comparative studies (in situ and in vitro) and for both apoptosis markers. Moreover, hrIL1β increased the apoptosis rate in vitro in a dose dependent manner in OA and normal chondrocytes. CONCLUSION—These results suggest that apoptosis may be an important factor in the evolution of OA and may be a new target for treatment of OA.